2009
DOI: 10.1111/j.1365-2893.2009.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C/HIV co-infection is associated with higher mortality in hospitalized patients with Hepatitis C or HIV

Abstract: Up to 10% of all patients with Hepatitis C virus (HCV) infection are co-infected with human immunodeficiency virus (HIV); 25-30% of HIV patients are co-infected with HCV. The aim of this study was to examine the association of HCV/HIV co-infection with outcomes of hospitalized patients compared to those with HCV or HIV monoinfection. Using the 2006 Nationwide Inpatient Sample, patients with HCV or HIV monoinfection or HCV/HIV co-infection were identified using ICD-9-CM codes. We compared liver-related and infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 27 publications
5
21
0
Order By: Relevance
“…6 A study using NIS 2006 found significantly higher mortality in HIV-HCV co-infection compared to HCV monoinfection. 7 While neither of these studies looked specifically at HBV inpatient mortality, HBV was associated with higher mortality in both ALD and HCV admissions from 1995 and was associated with higher frequency of hospitalisation in the 2006 data. 6,7 To our knowledge, there has not been a comparison of mortality and other outcomes such as length of stay and costs for HBV, HCV, and ALD from a nationwide representative sample of hospitalised patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A study using NIS 2006 found significantly higher mortality in HIV-HCV co-infection compared to HCV monoinfection. 7 While neither of these studies looked specifically at HBV inpatient mortality, HBV was associated with higher mortality in both ALD and HCV admissions from 1995 and was associated with higher frequency of hospitalisation in the 2006 data. 6,7 To our knowledge, there has not been a comparison of mortality and other outcomes such as length of stay and costs for HBV, HCV, and ALD from a nationwide representative sample of hospitalised patients.…”
Section: Resultsmentioning
confidence: 99%
“…7 While neither of these studies looked specifically at HBV inpatient mortality, HBV was associated with higher mortality in both ALD and HCV admissions from 1995 and was associated with higher frequency of hospitalisation in the 2006 data. 6,7 To our knowledge, there has not been a comparison of mortality and other outcomes such as length of stay and costs for HBV, HCV, and ALD from a nationwide representative sample of hospitalised patients. In view of the changing epidemiology of the three diseases, an updated comparison of the relative outcomes and costs of hospitalisations associated with the three groups will be useful to inform healthcare resource utilisation and prediction of future costs.…”
Section: Resultsmentioning
confidence: 99%
“…Patients that are dually infected tend to experience accelerated progression of end-stage liver disease leading to increased risk of morbidity and mortality [5,6,19-21]. This distinction is important given their unique, clinical needs.…”
Section: Discussionmentioning
confidence: 99%
“…While antiretroviral and antiviral therapies are widely recommended for use in patients with coinfection [4], these patients continue to experience poorer health outcomes than those with monoinfection. For instance, these individuals are at increased risk for accelerated progression of liver disease and increased rates of morbidity and mortality [5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…HBV/HIV coinfection is associated with an increased risk of all‐cause and liver‐related hospitalizations . Prior studies have demonstrated that hepatitis C (HCV)/HIV coinfection increases the risk of in‐hospital liver‐related death, especially among patients with cirrhosis and portal hypertension . A study by Puoti et al .…”
Section: Introductionmentioning
confidence: 99%